Ethical leadership - Lapuzina, Olena Mykolayivna; Mukuni, Joseph (My University, 2023)
The theoretical, methodical and practical issues of leadership ethics of a modern specialist, its nature, essence and basic principles are considered. Theoretical and practical recommendations are provided that will help to operate successfully in the conditions of the market economy. The manual is intended for students of all majors who are studying the leadership course, and can also be useful for teachers of psychological and pedagogical and managerial disciplines, specialists in other fields of science and production.
Keywords: educational guide; business negotiations; corporate ethics; ecological ethics; technoethics; ethics of presentations